1991
DOI: 10.1183/09031936.93.04080945
|View full text |Cite
|
Sign up to set email alerts
|

Total respiratory resistance and reactance in ankylosing spondylitis and kyphoscoliosis

Abstract: Ankylosing spondylitis and kyphoscoliosis both alter the function of the lung by modifying the mechanical properties of the thoracic cage. The purpose of the present study was to assess the changes in total respiratory resistance (Rrs) and reactance (Xrs) in these patients and to compare these data with conventional pulmonary function tests. In 16 patients with ankylosing spondylitis and seven with kyphoscoliosis we measured lung volumes, maximal flows, diffusing capacity, airway resistance, lung compliance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(6 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The increase in resistance values (Figure 1) are in line with the observed increase in Raw evaluated by body plethysmography. These findings are in line with those obtained by van Noord et al (8), which attributed the increase to a marked decrease in pulmonary volume. A similar decrease in pulmonary volume was observed in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The increase in resistance values (Figure 1) are in line with the observed increase in Raw evaluated by body plethysmography. These findings are in line with those obtained by van Noord et al (8), which attributed the increase to a marked decrease in pulmonary volume. A similar decrease in pulmonary volume was observed in the present study (Table 2).…”
Section: Discussionsupporting
confidence: 93%
“…Measurements of chest wall recoil are seldom performed in clinical practice because it is very difficult to obtain reliable data in untrained subjects. Therefore, the ability of oscillometry in providing information on the mechanical behavior of airways, lungs, and chest wall is of special interest in the analysis of patients with scoliosis (8). Although this method has been successfully applied to improve our understanding of abnormal respiratory mechanics in several diseases (6), there are few data in the literature about the use of oscillometry in scoliosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors not only hinder patient mobility but also restrict respiratory capacity [ 16 , 17 ]. This issue is much more prominent in cases with AS and accompanying spine deformities like kyphoscoliosis that multiplies the challenges due to cervical spine and temporomandibular joint mobility limitations and further restrictions in respiratory capacity as in these complex cases the thoracolumbar spine is severely affected and deformed [ 12 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rigidity of the chest and its joints combined with pain and an abnormal respiratory pattern may lead to decreasing pulmonary function [ 27 ] and weakening respiratory muscles [ 28 ]. Research conducted by Sahin et al [ 29 ] revealed that AS patients were characterized by significantly lower chest expansion, respiratory muscle weakness, FVC and FEV1 parameters.…”
Section: Discussionmentioning
confidence: 99%